2019
DOI: 10.4236/ijmpcero.2019.82011
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Comparison between Three Dimensional Conformal Radiation Therapy (3DCRT) & Intensity Modulated Radiation Therapy (IMRT) in Mid-Lower Oesophageal Carcinoma

Abstract: Purpose: To investigate if intensity modulated radiation therapy (IMRT) offers a better planning target volume (PTV) coverage and/or lower dose to normal thoracic structures in comparison to three dimensional conformal radiation therapy (3DCRT) in the treatment of mid and lower oesophageal carcinoma patients. Materials and Methods: A prospective study in the period from 2014 till 2015 was held in the radiation therapy department of the National Cancer Institute, Cairo University, in which 20 locally advanced o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Thus, radiation dose escalation has been proposed as a more effective substitute to improve local-regional and survival rates, especially in Asian population [7] [8] [9]. Additionally, two-dimensional radiotherapy (2D-RT) technology, which has apparent dosage deficiency and cold spots compared with modern radiotherapy techniques [10], thus questions have been raised as to whether dose escalation utilizing computerized tomography (CT)-based radiotherapy approaches could bring about survival benefits with less treatment-related toxicity in the 3D-RT era. In recent years, numerous studies or pooled meta-analyses showed that escalated radiation dose could improve local control (LC) and OS with no increase in serious adverse radiation-related toxicities, raising the possibility that this factor may be advantageous in dCRT [7] [8] [9] [11]- [17].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, radiation dose escalation has been proposed as a more effective substitute to improve local-regional and survival rates, especially in Asian population [7] [8] [9]. Additionally, two-dimensional radiotherapy (2D-RT) technology, which has apparent dosage deficiency and cold spots compared with modern radiotherapy techniques [10], thus questions have been raised as to whether dose escalation utilizing computerized tomography (CT)-based radiotherapy approaches could bring about survival benefits with less treatment-related toxicity in the 3D-RT era. In recent years, numerous studies or pooled meta-analyses showed that escalated radiation dose could improve local control (LC) and OS with no increase in serious adverse radiation-related toxicities, raising the possibility that this factor may be advantageous in dCRT [7] [8] [9] [11]- [17].…”
Section: Introductionmentioning
confidence: 99%